The PGPR strain Phyllobacterium brassicacearum STM196 induces a reproductive delay and physiological changes that result in improved drought tolerance in Arabidopsis. Issue 2 (4th July 2013) - Bresson, Justine; Varoquaux, Fabrice; Bontpart, Thibaut; Touraine, Bruno; Vile, Denis
Summary: Understanding how biotic interactions can improve plant tolerance to drought is a challenging prospect for agronomy and ecology. Plant growth‐promoting rhizobacteria (PGPR) are promising candidates but the phenotypic changes induced by PGPR under drought remain to be elucidated. We investigated the effects of Phyllobacterium brassicacearum STM196 strain, a PGPR isolated from the rhizosphere of oilseed rape, on two accessions of Arabidopsis thaliana with contrasting flowering time. We measured multiple morphophysiological traits related to plant growth and development in order to quantify the added value of the bacteria to drought‐response strategies of Arabidopsis in soil conditions. A delay in reproductive development induced by the bacteria resulted in a gain of biomass that was independent of the accession and the watering regime. Coordinated changes in transpiration, ABA content, photosynthesis and development resulted in higher water‐use efficiency and a better tolerance to drought of inoculated plants. Our findings give new insights into the ecophysiological bases by which PGPR can confer stress tolerance to plants. Rhizobacteria‐induced delay in flowering time could represent a valuable strategy for increasing biomass yield, whereas rhizobacteria‐induced improvement of water use is of particular interest in multiple scenarios of water availability.